PENGARUH BUDAYA ORGANISASI DAN LINGKUNGAN KERJA TERHADAP MOTIVASI KERJA SERTA DAMPAKNYA TERHADAP KEPUASAN KERJA KARYAWAN - Cici Bela Saputri; Baribin, Diah Pranitasari (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2020)
This study aims to determine (1) The influence of organizational culture on the work motivation of PT Posmi Steel Indonesia's employees, (2) The influence of the work environment on the work motivation of PT Posmi Steel Indonesia's employees, (3) The influence of organizational culture on PT Posmi Steel Indonesia's employee job satisfaction, (4) The influence of the work environment on PT Posmi Steel Indonesia's employee job satisfaction, (5) The effect of work motivation on PT Posmi Steel Indonesia's employee job satisfaction, (6) The influence of organizational culture and work environment on the work motivation of PT Posmi Steel Indonesia's employees, and ( 7) The influence of organizational culture and work environment on work motivation and job satisfaction of employees of PT Posmi Steel Indonesia. The sample used in this study were 215 respondents from permanent employees of PT. Posmi Steel Indonesia. The statistical tests used are validity, reliability and path analysis. The calculation results show that: (1) organizational culture has a significant effect on the work motivation of PT Posmi Steel Indonesia's employees, (2) the work environment has a significant effect on the work motivation of PT Posmi Steel Indonesia's employees, (3) organizational culture has a significant effect on job satisfaction of PT Posmi employees Steel Indonesia, (4) Work environment has a significant effect on job satisfaction of PT Posmi Steel Indonesia's employees, (5) Work motivation has a significant effect on job satisfaction of PT Posmi Steel Indonesia's employees, (6) Organizational culture and work environment have a significant effect on the work motivation of PT employees Posmi Steel Indonesia, and (7) Organizational culture and work environment significantly influence work motivation and job satisfaction of PT Posmi Steel Indonesia employees.